P11 Review of pregnancy outcomes in patients with ankylosing spondylitis presenting to the Bart's Health High Risk Antenatal clinic: results of clinical audit and recommendations. (20th April 2020) - Khudadah, Mohammad; Jansz, Sabrina; Saeed, Aamir; Bickerstaff, Maria
Abstract: Background: Most patients with ankylosing spondylitis are diagnosed in their reproductive years and pregnancy can pose a challenge for the physician. Referral for preconception counselling, monitoring and management of these patients is best done in a multidisciplinary specialist clinic. To date, literature does not associate AS with adverse effects on pregnancy outcome. Patients can have unchanged, improved or active disease during pregnancy, however, postpartum flare is common. Methods: We conducted a retrospective audit looking at pregnancy outcomes in patients referred to the High Risk Antenatal Clinic (HR-ANC) in our Trust between January 2014 and September 2019. Results: A total of 18 patients with 22 pregnancies were found on our electronic system. Analysis showed an average number of visits to the clinic of 3.4 visits per patient with a median of 4. Only 45% had some form of preconception counselling prior to referral. 41% of the pregnancies were not exposed to any regular medications prior to conception. All other patients had their medications stopped after conception. 59% of pregnancies had medical induction of labour, 23% had a caesarian section. Median delivery was 39 weeks. The average birth weight was 3, 022 grams, median 3, 205 grams. 59% of the patients had antenatal disease flare and 45% had a postpartum flare. 32% of pregnancies did not have postpartum follow up. Conclusion: Appropriate and thorough counselling should be offered to all patients with emphasis on disease course and management, safety of medications and neonatal vaccinations. Patients should be aware of a high chance of having active disease during pregnancy and the postpartum period. The rate of caesarian section in our patient cohort was not increased compared to the local rates in low risk pregnancies. These findings of disease activity in the antenatal and postpartum periods are consistent with published data. Good monitoring in a multidisciplinary clinic can lead to a successful outcome. Based on our findings, we are setting up a formal preconception counselling clinic for patients with AS with the following aims: 1. Family planning, including contraception advice. 2. Advice regarding medication use in the preconception, antenatal and postpartum periods. 3. Advice regarding disease course and expectations. 4. Advice regarding neonatal vaccinations, especially in patients on biological treatment. 5. Hot line for unplanned pregnancy and advice regarding medications and referral to the HR-ANC. Disclosures: M. Khudadah None. S. Jansz None. A. Saeed None. M. Bickerstaff None.